Rereading 1 Kings 17:21 in Light of Ancient Medical Texts - Davis, Andrew R. (Journal of Biblical literature, 2016)
This article proposes a new reading of the verb ṿayitmoded in 1 Kgs 17:21 which, I argue, is not from mdd ("to measure") but from myd ("to shake"). I begin by showing that the current understanding of the verb from mdd , which in this verse is usually translated "to stretch," is problematic. I suggest that the root myd , which occurs in Hab 3:6, offers a viable alternative to this problematic reading. Finally, comparing this action to Mesopotamian protocols for diagnosing comas, I propose that Elijah shakes himself over the comatose boy in order to determine his condition. This diagnosis then informs Elijah's prayer for YHWH to return the boy's nfsh, which is exactly what happens in the next verse. In this reading, Elijah's action is neither therapeutic nor magical; it is diagnostic and a necessary step that enables Elijah to formulate a prayer that is specific to the boy's predicament. His revival is not achieved through Elijah's self-measurement or sympathetic magic; rather it is the result of the prophetic word, which has the power to move YHWH to action.